Study of suitable illumination techniques for solder dot volume measurement on printed circuit card assembly - Sopajarn, Jerawat; Thongnoo, Krerkchai; Karnjanadecha, Montri (Asia-Pacific Journal of Science and Technology, 2017)
This research is the study of the suitable illumination Techniques for solder dot volume measure menton printed circuitcard assembly (PCCA). The measurement was based on image processing techniques. The solder images were captured from several controlled conditions, such as light conditions, and focus positions. These capturedimages were then analyzed based on the relationship of the captured images, and the solder dots volume was fiallycalculated .It is found thatthe dark fild lightsource with the reflctoris the mostsuitable lightsource when it was compared to the dome bright fild light source and the dark fild light source with out the reflctor. The measured volume was then compared to the volume measure dusing as canning electron microscope. Without the image processingcorrection, the accuracy of the measured solder volume was about 44%. However, withthe image processing correction atthe suitable lightintensity, the accuracy was increasedup to 70%.